2013
DOI: 10.1371/journal.pone.0078322
|View full text |Cite|
|
Sign up to set email alerts
|

Triglyceride-Rich Lipoprotein Modulates Endothelial Vascular Cell Adhesion Molecule (VCAM)-1 Expression via Differential Regulation of Endoplasmic Reticulum Stress

Abstract: Circulating triglyceride-rich lipoproteins (TGRL) from hypertriglyceridemic subjects exacerbate endothelial inflammation and promote monocyte infiltration into the arterial wall. We have recently reported that TGRL isolated from human blood after a high-fat meal can elicit a pro- or anti-atherogenic state in human aortic endothelial cells (HAEC), defined as up- or down-regulation of VCAM-1 expression in response to tumor necrosis factor alpha (TNFα) stimulation, respectively. A direct correlation was found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 40 publications
4
42
0
1
Order By: Relevance
“…In addition, MCP‐1 secretion is reduced by SAL in gLDL‐exposed HEC. Reported data show that eIF2α/CHOP pathway activated by ERS is important for the stimulation of VCAM‐1 and MCP‐1 production in other experimental models . Interestingly, in agreement with these studies, we have previously revealed that in HEC after 24 h incubation with gLDL, only eIF2α/CHOP pathway of the unfolded protein response remains upregulated .…”
Section: Discussionsupporting
confidence: 84%
“…In addition, MCP‐1 secretion is reduced by SAL in gLDL‐exposed HEC. Reported data show that eIF2α/CHOP pathway activated by ERS is important for the stimulation of VCAM‐1 and MCP‐1 production in other experimental models . Interestingly, in agreement with these studies, we have previously revealed that in HEC after 24 h incubation with gLDL, only eIF2α/CHOP pathway of the unfolded protein response remains upregulated .…”
Section: Discussionsupporting
confidence: 84%
“…Stromal endothelial cells exposed to the oxidized lipid 1-palmitoyl-2-arachidonoyl-sn-3-glycero-phosphorylcholine, often found in atherosclerotic lesions, upregulate the monocyte chemoattractant CXCL3 in an XBP-1-dependent manner (141). Similarly, in response to proatherogenic triglyceride-rich lipoprotein, endothelial cells induce VCAM-1 via CHOP, potentially enhancing adhesion and diapedesis of lymphocytes, myeloid cells, and granulocytes (142). Furthermore, both muscle cells and airway epithelial cells secrete a functional leukocyte-adhesive hyaluronan matrix after exposure to various forms of ER stress (143).…”
Section: Stromal Cell Damage and The Extracellular Milieumentioning
confidence: 99%
“…It has been confirmed that ER stress is induced in atherosclerosis lesions[24, 25]. A previous study indicated that ER stress accelerated atherosclerosis through promoting macrophage-derived foam cell formation[26], inducing apoptosis of lesion-resident macrophages[27], accelerating smooth muscle cell proliferation[28], and stimulating the secretion of inflammatory cytokines, adhesion and apoptosis in endothelial cells[29, 30]. These observations are in agreement with the results of the present study.…”
Section: Discussionmentioning
confidence: 93%